2018
DOI: 10.2196/10754
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adherence to Internet-Delivered Psychotherapy for Symptoms of Depression and Anxiety After Myocardial Infarction: Machine Learning Insights From the U-CARE Heart Randomized Controlled Trial

Abstract: BackgroundLow adherence to recommended treatments is a multifactorial problem for patients in rehabilitation after myocardial infarction (MI). In a nationwide trial of internet-delivered cognitive behavior therapy (iCBT) for the high-risk subgroup of patients with MI also reporting symptoms of anxiety, depression, or both (MI-ANXDEP), adherence was low. Since low adherence to psychotherapy leads to a waste of therapeutic resources and risky treatment abortion in MI-ANXDEP patients, identifying early predictors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 44 publications
2
43
0
2
Order By: Relevance
“…Several studies have shown that certain covariates at the participant level, such as adherence to the intervention, participant age, or gender [ 41 - 43 ], can influence dropout rates and intervention success. It is also of interest whether the use of the intervention or the amount of contact with the study team influenced the changes in the outcome measures.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that certain covariates at the participant level, such as adherence to the intervention, participant age, or gender [ 41 - 43 ], can influence dropout rates and intervention success. It is also of interest whether the use of the intervention or the amount of contact with the study team influenced the changes in the outcome measures.…”
Section: Methodsmentioning
confidence: 99%
“…A study was done by Garcia et al [59] outlines several studies done about mental health monitoring system that uses sensors and machine learning. Similarly, ML-based algorithms have been used to predict user adherence to IDPT for depression and anxiety after myocardial infarction [74]. The use of MLbased predictive algorithms can be used to increase adaptation in IDPT systems, and the overall process is illustrated in Figure 6.…”
Section: Adaptation Through Predictive Algorithmsmentioning
confidence: 99%
“…The same study concluded that pattern recognition can be a useful tool to tailor interventions based on usage patterns from earlier lessons [ 56 ]. With the hype of data science, several studies [ 12 , 40 , 44 , 49 , 50 , 58 , 60 - 62 ] attempted to use some form of predictive algorithm to adapt the intervention. While some studies did not report the outcome of the overall study [ 40 , 49 ], most of them reported that the use of predictive algorithms had a positive effect on the adaptation of interventions [ 12 , 44 , 50 , 58 , 60 - 62 ].…”
Section: Resultsmentioning
confidence: 99%